Hybridity and Representation in an Ancient Mediterranean Context: The Cultures In-Between Cypriote Culture - Counts, Derek B. (My University, 2006)
This working paper examines the art, culture, and religion of ancient Cyprus in order to study the ancient Mediterranean in the context of a global community.
Keywords: globalization; ancient history; Mediterranean; Cyprus; art; culture